Facing climate variability in sub-Saharan Africa: analysis of climate-smart agriculture opportunities to manage climate-related risks - Zougmoré, Robert B.; Partey, Samuel T.; Ouédraogo, Mathieu; Torquebiau, Emmanuel F.; Campbell, Bruce M. (EDP Sciences, 2018)
In the literature, a lot of information is available about climate change perceptions and impacts in sub-Saharan Africa. However, there is limited attention in the region to emerging initiatives, technologies and policies that are tailored to building the adaptive capacity of agricultural systems to climate change and variability. In this paper, we discuss the prospects for climate-smart agriculture technologies and enabling policies in dealing with climate change and variability at different sub-regional levels of sub-Saharan Africa to sustain farm productivity and livelihoods of agrarian communities. The review provides substantial information suggesting that without appropriate interventions, climate change and variability will affect agricultural yields, food security and add to the presently unaceptable levels of poverty in sub-Saharan Africa. Although some of them were already existing, the past decades have seen the development and promotion of climate-smart agriculture innovations such as the use of high yielding drought tolerant crop varieties, climate information services, agricultural insurance, agroforestry, water harvesting techniques, integrated soil fertility management practices, etc. In the context of climate change, this appears as a stepping up approach to sustainably improving farm productivity, rural livelihoods and adaptive capacity of farmers and production systems while contributing to mitigation. The development of regional, sub-regional and national climate change policies and plans targeted at mitigating climate change and improving adaptive capacity of the African people have also been developed to enable mainstreaming of climate-smart agriculture into agricultural development plans. Financial commitments from governments and development agencies will be crucial for improving large-scale adoption of climate-smart agriculture.